Neuromarketing Unlocked: Harnessing Brain Science to Decode Consumer Insights - Rahaman, Shafeeq Ur; Kumar, Saurabh; Puchakayala, Praneeth Reddy Amudala (International Journal of Computing and Engineering, 2021)
Purpose: This study aims to highlight the potential applications of neuromarketing tools and technologies including fMRI, EEG, eye-tracking and GSR to explore their effectiveness in enhancing consumer engagement. The study also calls for the establishment of ethical guidelines, data privacy protections and transparency in neuromarketing. Methodology: In this paper, a systematic literature review and analysis of empirical studies utilizing neuromarketing tools was employed. Relevant case studies were selected to illustrate the application and effectiveness of neuromarketing tools. Ethical concerns like consumer manipulation, informed consent, and the protection of vulnerable populations were also reviewed. Findings: The study identifies the potency of neuromarketing tools in enhancing consumer insights by targeting subconscious responses. Different real-time cases demonstrate the integrity of various tools of neuromarketing in marketing campaigns and how this triggered a tremendous change in consumer engagement and loyalty. This paper also seeks to strike a balance between applying neuromarketing approaches and addressing its ethical implications in modern marketing practices. Contribution to Theory, Policy and Practice: This study contributes to the evolving field of neuromarketing by depicting the interplay between neuroscience and marketing strategies. It advances the theoretical understanding of how consumer behavior can be scientifically analyzed in direct relation to psychological and emotional drivers that influence decisions. The study also emphasizes the importance of data privacy, informed consent, and transparency in marketing practices.